Integrated Information System for Livestock Health Data Management - Ramadhan, Sayzajaya (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2025)
The growing demand for efficient livestock management highlights the importance of reliable health data systems that support decision-making and disease prevention. However, many existing approaches still rely on fragmented and manual processes, leading to inaccuracies, delays, and limited collaboration among stakeholders such as farmers, veterinarians, and government officers. This study proposes an Integrated Information System for Livestock Health Data Management designed to centralize health records, streamline data entry, and enhance reporting accuracy. The system employs structured data modeling through class diagrams, flowcharts, and interface designs to capture farmer reports, veterinary diagnoses, and administrative validations in a coordinated workflow. By integrating these processes, the solution ensures seamless data flow, reduces redundancy, and fosters collaboration across roles. The results demonstrate improved data consistency, faster response times, and stronger support for monitoring livestock health. This approach provides a practical and replicable framework to modernize livestock health management systems.